2001
DOI: 10.1111/j.1559-1816.2001.tb00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Violent Versus Nonviolent Video Games on Children's Arousal, Aggressive Mood, and Positive Mood

Abstract: This study investigated the relationship between violent video games and children's mood. A total of 71 children aged 8 to 12 years played a paper-and-pencil game, a nonviolent video game, and a violent video game. Results indicate that arousal, as measured by heart rate and self-reported arousal, increased significantly after playing the violent video game, as compared with the other two game conditions, with girls reporting more arousal than did boys. There was no significant increase in aggressive mood scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 54 publications
1
48
0
7
Order By: Relevance
“…Violent media content can induce intense arousal in children (Bushman & Huesmann, 2006;Fleming & Rickwood, 2001). However, after repeated exposure, children may get desensitized to media violence, which means that they gradually experience less induced arousal to the same violent media portrayals (Ballard, Hamby, Panee, & Nivens, 2006).…”
Section: Violent Contentmentioning
confidence: 99%
“…Violent media content can induce intense arousal in children (Bushman & Huesmann, 2006;Fleming & Rickwood, 2001). However, after repeated exposure, children may get desensitized to media violence, which means that they gradually experience less induced arousal to the same violent media portrayals (Ballard, Hamby, Panee, & Nivens, 2006).…”
Section: Violent Contentmentioning
confidence: 99%
“…Lab studies have shown that computer and console game players have increased heart rate, blood pressure, and oxygen consumption after playing. In addition, these effects are greater after engaging in electronic play than they are after engaging in more traditional activities such as watching television, reading, or listening to music (Fleming & Rickwood, 2001). Since heightened arousal can amplify predisposed responses, it is possible that even subtle effects of electronic play could have a greater impact on behavior than other types of play, for individuals who display trait aggression or aggressive personality.…”
Section: Trait Aggressionmentioning
confidence: 99%
“…A pesquisa tem evidenciado que os jogos de acção, entre os quais se incluem os de violência, têm tendência para desencadear um aumento de activação fisiológica face a níveis de registo iniciais (e.g., Anderson et al, 2004). Por outro lado, os jogos violentos tendem a ser mais activadores do sistema nervoso autónomo do que jogos não violentos e sem acção (e.g., Fleming & Rickwood, 2001).…”
Section: Efeitos Imediatos Da Participação Em Jogos Violentos Na Agreunclassified
“…Em geral, os estados afectivos são medidos através de auto-avaliações, solicitando-se aos participantes que referiram a forma como se sentiram durante ou após o jogo, e, em desenhos intra-sujeitos, antes de o iniciarem. Estados afectivos positivos e negativos têm sido avaliados (e.g., Fleming & Rickwood, 2001), embora seja mais frequente a operacionalização dos estados de hostilidade (e.g., Anderson & Dill, 2000;Wingrove & Bond, 1998). Para avaliar a acessibilidade a construtos agressivos, os autores têm recorrido a tarefas de processamento de informação, que têm a vantagem de evitar os problemas associados aos testes de autoavaliação.…”
Section: Efeitos Imediatos Da Participação Em Jogos Violentos Na Agreunclassified